A protocol for rarid grain size analysis by electronic pippet. A new approach - Αλμπανάκης, Κωνσταντίνος (Bulletin of the Geological Society of Greece, 2011)
In this article, the author suggests the creation of a protocol for grain size distribution analysis by pipette method, using specialized software and hardware for minimizing the time needed for analysis. The suggested protocol needs less than 45 minutes for analyzing the size distribution 4Φ to 8Φ sizes since it uses short setting distances, in relation to small pipetting volume, with increased volumetric accuracy and weighting. An Eppendorf Multipette® Stream, electronic pipette, was used with syringe type tips of 2.5 ml. The tip of this electronic pipette was modified and extended, to create a usable length of 6 cm. Small cylindrical setting tubes, 170 ml, were constructed from transparent Plexiglas, with a special cap on the top, to help smooth insertion of the pipette tip. The electronic pipette was programmed to disperse exactly 2000 μl out of 2500 μl of the total tip. Each 2000 μl pipetting had and accuracy in the order of +/- 4 μl. The samples were placed into small metallic containers and placed on top of heating plates with temperature of 65ο C, for drying. The small volume of the samples accelerates further the whole process. The weighting was performed by an electronic balance with a resolution of 0.1 μl. Using Folk (1980) equation, for setting time calculation and tables for temperature dependence of the setting time, the author created an equation that approximates the settling time for each grain size with temperature. The equation is: